2016
DOI: 10.1007/s00027-016-0476-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of river scale flow regimes and local scale habitat properties on fish community attributes

Abstract: Community attributes result from processes operating at various spatial scales. The hierarchic organisation of rivers and the prevailing hypotheses about the variables that affect fish communities make lotic ecosystems particularly suitable to study processes taking place across spatial scales. The general goal of this study was to investigate how river flow regime and local habitat properties explain and predict fish community attributes in unregulated and regulated rivers. Our objectives were: (1) to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Hydro-peaking rivers additionally provoke frequent and rapid flow peaks that are timed to match daily consumption needs, causing significant flow alteration (Zimmerman et al, 2010) and subsequent ecological impacts (Bond, Jones & Haxton, 2015;Macnaughton et al, 2015b;Senay et al, 2016). All unregulated and regulated rivers segments were analysed together to assess the effect of contrasting river flow and thermal regimes on fish guild models.…”
Section: River Segments Sites and Surveying Methodologymentioning
confidence: 99%
“…Hydro-peaking rivers additionally provoke frequent and rapid flow peaks that are timed to match daily consumption needs, causing significant flow alteration (Zimmerman et al, 2010) and subsequent ecological impacts (Bond, Jones & Haxton, 2015;Macnaughton et al, 2015b;Senay et al, 2016). All unregulated and regulated rivers segments were analysed together to assess the effect of contrasting river flow and thermal regimes on fish guild models.…”
Section: River Segments Sites and Surveying Methodologymentioning
confidence: 99%
“…For example, even small, but repeated, flow fluctuations were found to decrease the feeding time, growth, and survival of fish (Young et al 2011). In addition, small but frequent anthropogenic fluctuations in flow have also been found to reduce fish density and biomass when compared to infrequent but large fluctuations generated by storage-reservoir hydropower in Canada (Senay et al 2016). These findings may be particularly relevant for RoR hydropower systems, which can create more frequent pulses in flow compared to reservoir-storage hydropower due to the lack of water storage in headponds and wider-magnitude fluctuations during low-flow seasons.…”
Section: Pathway 3: Anthropogenic Flow Fluctuationsmentioning
confidence: 96%
“…Data from an unregulated montane stream in the US Pacific Northwest show that natural fluctuations in stage rarely exceeded 5 cm·h −1 (Hunter 1992, cited in Bell et al 2008, while frequent declines in river stage of 80-90 cm over 10 min were reported downstream of a reservoir-storage dam in Norway (Hvidsten 1985). Fish stranding or isolation in side channels may in turn lead to negative effects on survival, biomass, density, or fitness, as reported in studies from reservoir-storage systems (Young et al 2011;Nagrodski et al 2012;Senay et al 2016). Given the limited research that has specifically sought to understand the consequences of anthropogenic flow fluctuations in RoR hydropower systems, large uncertainties remain about how their effects differ from those documented downstream of reservoir-storage systems where most peer-reviewed research has occurred.…”
Section: Pathway 3: Anthropogenic Flow Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations